2004
DOI: 10.1021/la047980b
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Photoelectron Spectroscopy and Near-Edge X-ray Absorption Fine Structure Study of Water Adsorption on Pyridine-Terminated Thiolate Self-Assembled Monolayers

Abstract: Adsorption of water on self-assembled monolayers (SAMs) of 4-(4-mercaptophenyl)pyridine on gold at low temperatures under ultrahigh vacuum conditions is studied by synchrotron radiation X-ray photoelectron and absorption spectroscopy. Water adsorption induces a strong modification of the chemical state of the pyridine N atoms at the SAM/ice interface, indicative for strong H bonding and partial proton transfer between water molecules and pyridine moieties. Additionally, the initial molecular orientation within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
109
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(131 citation statements)
references
References 31 publications
22
109
0
Order By: Relevance
“…Such a shift has been observed in pyridine-terminated SAMs on Au substrates, in which the C 1s emissions related to the carbon atoms in the ortho and para positions of the pyridine were observed at 285.3-286.6 eV. [42] A single emission in the N 1s spectrum related to nitrogen atom incorporation into the aromatic rings is observed at a BE of 399.0 eV for both PPPT/Au and PPPT/Ag. This BE is very close to the value expected for an unmodified pyridine moiety (ca.…”
Section: Xps and Nexafs Characterizationmentioning
confidence: 62%
“…Such a shift has been observed in pyridine-terminated SAMs on Au substrates, in which the C 1s emissions related to the carbon atoms in the ortho and para positions of the pyridine were observed at 285.3-286.6 eV. [42] A single emission in the N 1s spectrum related to nitrogen atom incorporation into the aromatic rings is observed at a BE of 399.0 eV for both PPPT/Au and PPPT/Ag. This BE is very close to the value expected for an unmodified pyridine moiety (ca.…”
Section: Xps and Nexafs Characterizationmentioning
confidence: 62%
“…Monte Carlo simulations and sum frequency generation (SFG) experiments have shown that hydrogen bonding to oxygen atoms of oligo(ethylene glycol)-terminated SAMs [31,32]. Pyridine-terminated SAMs are strongly affected by water adsorption where H bonding and partial proton transfer was observed [33].…”
Section: Discussionmentioning
confidence: 99%
“…5B) is indicative of a single species and suggests that the complex adsorbs intact. The binding energy indicates an iron(II) species [65], as inferred from comparison with other complexes where the iron(II) ion is coordinated to nitrogen ligands, such as phthalocyanines or porphyrins [66,67]. That the complex adsorbs intact may also be inferred from the nitrogen signal, whose intensity is close to the stoichiometric ratio.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 93%